Improved electrical and thermal conductivities of polysiloxane-derived silicon oxycarbide ceramics by barium addition. Issue 2 (February 2018) - Eom, Jung-Hye; Kim, Young-Wook; Kim, Kwang Joo; Seo, Won-Seon
Abstract: The electrical and thermal conductivities of bulk barium-added silicon oxycarbide (SiOC-Ba) ceramics are investigated. The SiOC-Ba ceramics exhibited improved electrical and thermal conductivities upon increasing the sintering temperature from 1450 °C to 1650 °C. Precipitation of graphitic carbon clusters observed by Raman spectroscopy and high-resolution transmission electron microscopy is attributed to the phase separation during the fabrication process. The increase in the electrical conductivity can be rationalized in terms of an increase in the density of the sp 2 CC bonds within the carbon clusters. The increase in the thermal conductivity is mainly attributed to the formation of interconnected graphitic clusters in the SiOC matrix and SiC embedded in the clusters. The electrical and thermal conductivities of the SiOC-Ba ceramics sintered at 1650 °C are 14.0 Ω −1  cm −1 and 5.6 W/m K, respectively, at room temperature. The electrical conductivity of SiOC-Ba sintered at 1550 °C is 5.3 Ω −1  cm −1 and 7.0 Ω −1  cm −1 at 2 and 300 K, respectively.